Sufistic Approach in Understanding Hadith: Ḥakīm al-Tirmidhī’s Viewpoint - Ahmad Tajuddin Arafat; Mutma'inah Mutma'inah; Hanik Rosyida (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2022)
This article studies al-Ḥakīm al-Tirmidhī’s viewpoints toward understanding hadith on his work “Nawādir al-Uṣūl fi Ma’rifat Aḥādīth al-Rasūl.” Using the content analysis approach, this study reveals that the primary purpose of transmitting hadith is that the hadith’s message is supposed to be practiced so that happiness in the hereafter can be achieved, not just transmitting hadith from one person to another without any practical implication. So, it not only orients on the chain of transmission but also profoundly understands the matan or its contents. He quotes some hadith in his works to expose the meaning and the essence contained in every hadith and hopes that it can be a guideline of sulūk for those who intend to get closer (taqarrub) to God. Hence, the Sufism viewpoint becomes his basic epistemology in understanding the hadith.Contribution: This article provides a new perspective of the hadith transmitter requirement according to al-Tirmidhī, namely, having a critical view towards everything that is heard and accepted. It also shows that understanding hadith is not just to reveal its meaning but a sulūk for those who want to get closer to Allah.